C.1 - India. Ministry of Finance (New Delhi, 2006)
This report contains following topics: General Review; Public Finance; Monetary and Banking Developments; Securities Markets; Prices and Food Management; External Sector; Industry; Agriculture; Infrastructure; Social Sectors etc.
Keywords: Economic survey - 2005 - 06